The Role of Social Worker Dedicating Unit on Children Social Welfare Program - Suryani, Suryani; Hardiati, Enni (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is to describe the role of social worker dedicating unit on giving guidance children social welfare program (PKSA), as national priority through presidential instruction No 3, 2010 on justifiable development. PKSA is designed to protect and give services for children basic right, covering love, protection, sustainable live, grow and develop, that of several reasons their family could not fulfil them. The PKSA implementator is social worker dedicating unit or volounteer, graduated from bachelor or full degree of social work school, through selection, education, and appointment as contract social worker. Research location in Jambi Municipality, because in that municipality found many children problems and social worker that guide in solving the problem. Data are analised with qualitative technique. The research finds that the existence of social worker as children problem solving guidance is diterminative on the succes of the program. The role of social worker is helpful in giving service and guidance to the children. The handicap factor is the location that far in distance and found only one social worker in one municipality, not in balance with the quantity and quality of the problem. The salary also too small and coming late, no motorbike facility that makes social worker working with less enthusiasm. The supporting factor is sinergy among stakeholders commited to children problem. It recommended to the ministry of social affairs, especially the directorate of children affairs, should keep the existence of social worker and add its quantity in every municipality given the number of the increasing children problem.